X‐Ray Investigation of the Thermal Expansion Coefficient of Cubic Gallium Nitride on 3C‐SiC (001)/Si (001) Substrates - As, Donat Josef; Meier, Falco; Mahler, Pascal; Meier, Cedrik (physica status solidi (b))
This work investigates the temperature dependence of the lattice constant a exp of cubic GaN/3C‐SiC/Si (001) epilayers grown at 740°C by plasma‐assisted molecular beam epitaxy is investigated. High resolution X‐ray diffraction is performed to determine the lattice constant, using an Anton–Paar DHS1100 stage to vary the sample temperature from 25°C to 900°C, calibrated against the underlying single‐crystalline silicon substrate. A linear increase in a exp with rising temperature is observed. The thermal expansion behaviour is modelled using Debye´s phonon dispersion. The fitted lattice parameters are used to calculate the thermal expansion coefficient (TEC). At room temperature the TEC is determined to be α Debye ≈ 5.25 × 10 −6 K −1 . We further compare the TEC of the cubic GaN epilayer to that of free‐standing hexagonal GaN using the crystallographic relationship of , demonstrating good agreement between both phases. Using literature values for the elastic constants of cubic GaN, the corresponding elastic moduli and Debye temperature Θ D are calculated. An average value of Θ D of ≈905 ± 25 K is obtained, which is very close to our experimental results. Moreover, tensile strain is found to be present in our sample at room temperature, leading to an increase in the TEC. The impact of strain on the thermal properties of cubic GaN is discussed.

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Third‐Order Susceptibility of Lithium Niobate: Influence of Polarons and Bipolarons - Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero (physica status solidi (b))
The third‐order susceptibility of lithium niobate (LiNbO 3 ) is calculated within a Berry‐phase formulation of the dynamical polarization based on the electronic structure obtained within density‐functional theory (DFT). Maximum values of the order of m V are calculated for photon energies between 1.2 and 2 eV, i.e., in the lower half of the optical bandgap of lithium niobate. Both free and bound electron (bi)polarons are found to lead to a remarkable enhancement of the third‐order susceptibility for photon energies below 1 eV.

Clean and Hydrogen‐Adsorbed AlInP(001) Surfaces: Structures and Electronic Properties - Glahn, Luis Joel; Ruiz Alvarado, Isaac Azahel; Neufeld, Sergej; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Ostheimer, David; Shekarabi, Sahar; Romanyuk, Oleksandr; Moritz, Dominik Christian; Hofmann, Jan Philipp; Jaegermann, Wolfram; Hannappel, Thomas; et al. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Photoluminescence Line‐Shape Analysis of Highly n‐Type Doped Zincblende GaN - Baron, Elias; Goldhahn, Rüdiger; Deppe, Michael; As, Donat Josef; Feneberg, Martin (physica status solidi (b))

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Electric Field Induced Raman Scattering at the Sb–InP(110) Interface: The Surface Dipole Contribution - Esser, Norbert; Schmidt, Wolf Gero (physica status solidi (b))

Tight‐binding model for the electronic and optical properties of nitride‐based quantum dots - Schulz, S.; Mourad, D.; Schumacher, Stefan; Czycholl, G. (physica status solidi (b))
Abstract Two slightly different, efficient tight‐binding (TB) models for the description of the electronic properties of nitride‐based semiconductor quantum dots (QDs) have been developed and applied to the calculation of the electronic one‐particle spectrum of these structures. Using these one‐particle QD‐states, dipole and Coulomb matrix elements can be calculated, from which the optical properties of these systems can be obtained. These TB calculations have been performed for nitride‐based QDs with a cubic zincblende structure and those with a wurtzite crystal structure. In this paper, we discuss the general methodology used and the results obtained for the electronic one‐particle states and energies, for the dipole and Coulomb matrix elements, and for the excitonic optical emission and absorption spectra.

Dislocation reduction in GaN grown on Si(111) using a strain-driven 3D GaN interlayer - Häberlen, Maik; Zhu, Dandan; McAleese, Clifford; Zhu, Tongtong; Kappers, Menno J.; Humphreys, Colin J. (physica status solidi (b))
In this paper we demonstrate a strain-driven GaN interlayer method to reduce dislocation densities in GaN grown on (111) oriented silicon by metal organic vapour phase epitaxy (MOVPE). In order to achieve crack-free GaN layers of reasonable thicknesses and dislocation densities it is crucial to integrate both dislocation reduction and strain management layers. In contrast to techniques like FACELO or nanoELO we show the in situ formation of GaN islands directly on the AlN nucleation layer without the need to deposit a SiO2 or SiNx mask. A graded AlGaN layer for strain management can be grown on top of this dislocation reducing 3D GaN inter-layer in order to achieve crack-free GaN layers grown on top of the AlGaN strain management layer. Furthermore, an additional SiNx layer for subsequent dislocation reduction can also be incorporated into the structure and is shown to efficiently reduce the dislocation density down to the low 10^9 cm^2. The structural properties of the 3D GaN island buffer layer and overgrown samples are studied by means of SEM, cross-sectional, and plan view TEM. Cathodoluminiscence in an SEM is employed to correlate the dislocation microstructure as observed by plan view TEM with luminescent properties.

Magnetic characterization of conductance electrons in GaN - Scholle, A.; Greulich-Weber, S.; As, Donat Josef; Mietze, Ch.; Son, N. T.; Hemmingsson, C.; Monemar, B.; Janzén, E.; Gerstmann, Uwe; Sanna, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (b))

Metal-insulator transition in Si(111)-(4 × 1)/(8 × 2)-In studied by optical spectroscopy - Speiser, E.; Chandola, S.; Hinrichs, K.; Gensch, M.; Cobet, C.; Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Richter, W.; Fleischer, K.; McGilp, J. F.; Esser, N. (physica status solidi (b))

Quantum Hall effect in long and in mobility adjusted GaAs/AlxGa1-xAs samples - Diaconescu, D.; Goldschmidt, A.; Reuter, Dirk; Wieck, A. D. (physica status solidi (b))

Disorder issues in metallic photonic crystals - Nau, D.; Schönhardt, A.; Bauer, C.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (b))

Interaction between localized and delocalized surface plasmon polariton modes in a metallic photonic crystal - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Martin, O. J. F.; Kuhl, J.; Giessen, H. (physica status solidi (b))

Hole and electron wave functions in self-assembled InAs quantum dots: a comparison - Reuter, Dirk; Kailuweit, P.; Roescu, R.; Wieck, A. D.; Wibbelhoff, O. S.; Lorke, A.; Zeitler, U.; Maan, J. C. (physica status solidi (b))

Sub-second electron spin lifetimes in quantum dots at zero applied magnetic field due to alignment of QD nuclei - Oulton, R.; Verbin, S. Yu.; Auer, T.; Cherbunin, R. V.; Greilich, A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. (physica status solidi (b))